Precoder and combiner design for generalized spatial modulation based multiuser MIMO systems - Brogueira, B. (2021)
Multiple input multiple output (MIMO) schemes based on generalized spatial modulations (GSM) have been widely considered as potential candidate techniques for next-generation wireless networks, as they can improve both spectral and energy efficiency. In this paper we propose a multi-user MIMO system, where a base station transmits precoded GSM symbols to several receivers. In the adopted GSM approach, multiple antennas transmit different high-level QAM symbols simultaneously. The precoder is designed in order to remove interference between users while an iterative algorithm is applied at the receiver to accomplish single-user GSM detection. Simulation results show that the presented GSM MU-MIMO approach is capable to effectively exploit a large number of transmit antennas deployed at the transmitter and also provide performance gains over conventional MU-MIMO schemes with identical spectral efficiencies.